Отраслевое и территориальное планирование в условиях крупного города - Докшевич В. И. Валентина Ивановна; Червова Л. Г. Лидия Георгиевна; Савенко В. Н. Валентина Николаевна; Ковалева А. И. (Киев, Наукова думка, 1984)
Авт. указаны на обороте тит. л.